T82. THE IMPACT OF SMOKING ON LIFE EXPECTANCY IN PSYCHOTIC DISORDERS, AN ELECTRONIC CASE REGISTER COHORT STUDY. (18th May 2020) - Chesney, Edward; Robson, Deborah; Patel, Rashmi; Shetty, Hitesh; Richardson, Sol; Chang, Chin-Kuo; McGuire, Philip; McNeill, Ann
Abstract: Background: Schizophrenia, schizoaffective disorder and bipolar affective disorder are associated with a life expectancy at birth that is 10–20 years shorter than in the general population. The prevalence of cigarette smoking in people with these disorders is very high, but the extent to which this accounts for differences in mortality is unclear. We addressed this issue by examining the effect of smoking on life expectancy and survival in a large electronic healthcare database of patients receiving secondary mental healthcare in South East London. Methods: Data on all patients with a diagnosis of schizophrenia, schizoaffective disorder or bipolar affective disorder from 1st January 2007 to 31st December 2018 was obtained. Smoking status was determined using unstructured text data extracted from electronic health records. Chiang's method of abridged life tables was used to calculate estimates of life expectancy at birth according to gender and most commonly recorded smoking status. Cox proportional hazards models were used to estimate mortality risk and adjusted for a broad range of demographic and clinical variables. Results: 21, 588 patients were included in the study of which 20, 155 (93.4%) were classified as either smokers (16, 717 [77.4%]) or non-smokers (3, 438 (15.9%]). 2, 434 (11.3%) participants died by the end of the observation period. In female patients, life expectancy at birth was 67.6 years in current smokers (95% CI: 66.4 to 68.8) and 74.9 years in non-smokers (95% CI: 72.8 to 77.0). In male patients, life expectancy at birth was 63.5 years in current smokers (95% CI: 62.5 to 64.5) and 68.5 years in non-smokers (95% CI: 64.4 to 72.6). Adjusted survival models showed that current smoking was associated with an increased risk of death, in both females (aHR = 1.42; 95% CI: 1.21–1.66) and males (aHR = 1.49; 95% CI: 1.25–1.79). Discussion: Smoking may account for a substantial proportion of the reduced life expectancy in patients with psychotic disorders. Interventions to reduce tobacco smoking in patients with psychosis may therefore improve life expectancy in this group.